2016
DOI: 10.2503/hortj.mi-121
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Contribution of Four Major Anthocyanins to Black Flower Coloring of Dahlia Petals

Abstract: The black flower color of dahlias (Dahlia variabilis) has been suggested to be attributed to a high accumulation of cyanidin (Cy)-based anthocyanins. A possible explanation for this effect is that Cy-based anthocyanins in dahlias contribute more to the black flower color than pelargonidin (Pg)-based anthocyanins by lowering petal lightness (L*) and chroma (C*), but no obvious evidence has been reported. In this study, four major anthocyanins accumulated in dahlia petals, 3,5-diglucoside (3,5diG) and 3-(6''-mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…3). Analysis of the crude extracts showed that the retention time of the peaks of anthocyanins in red single-colored petals and the red part of bicolor petals was the same as in 'Kokucho' petals (data not shown), which mainly accumulate pelargonidin 3-(6''-malonylglucoside)-5glucoside and cyanidin 3-(6''-malonylglucoside)-5-glucoside (Deguchi et al 2016).…”
Section: Comparison Of Pigments In Bicolor and Red Petalsmentioning
confidence: 97%
“…3). Analysis of the crude extracts showed that the retention time of the peaks of anthocyanins in red single-colored petals and the red part of bicolor petals was the same as in 'Kokucho' petals (data not shown), which mainly accumulate pelargonidin 3-(6''-malonylglucoside)-5glucoside and cyanidin 3-(6''-malonylglucoside)-5-glucoside (Deguchi et al 2016).…”
Section: Comparison Of Pigments In Bicolor and Red Petalsmentioning
confidence: 97%
“…Regarding color intensity, EPAA presented the highest values in L* (lightness), a* (redness), and b* (yellowness), for a bright red/yellow tone (L* = 26.81, a* = 59.47, b* = 45.72), while in the case of EPMA, the color was red/blue (dark red) without brightness (L* = 2.15, a* = 12.90, b* = 3.28), resulting in an intense dark color (Table 3). Coordinates for L*, a*, and b* with a tendency to red color have been previously reported for purified fractions of anthocyanin solutions at pH 3 and measured immediately after dilution from different dahlia cultivars (around 70, 30.14, and 16.62, respectively) (Deguchi et al, 2016). On the other hand, the coordinates of EPAA extract show greater similarity to the L* and a* coordinates reported for the Red 40 L*(45.74), a*(45.14), b*(10.58) (Hernández-Martínez et al, 2017), which also indicates a brilliant red hue.…”
Section: Total Anthocyanin Content Antioxidant Activity and Colormentioning
confidence: 88%
“…78) displaying black coloration in the variegation that accumulated the largest TA than the other cyanic cultivars (Tables 1 and 2). The black-colored carnation flowers are likely due to the high concentration of Cy-based anthocyanin the same as in blackflowered dahlias (Deguchi et al, 2016). Interestingly, there were no cultivars composed of Cy-based anthocyanins with Ch2'G as the major flower pigment, which yields a maroon flower color (Yamaguchi, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Yamaguchi (1992) introduced an interspecific hybrid of D. caryophyllus and other Dianthus species with flowers possessing center spots and base parts accumulating Cy-based and Pg-based anthocyanins, respectively. There are some ornamental flowers that accumulate both Pg-and Cy-based anthocyanins as major flower pigments and the varying ratios of Pg and Cy extend the flower color range (Iwata et al, 1985;Torskangerpoll et al, 2005;Deguchi et al, 2016). However, carnation cultivars accumulate either Pg-or Cy-based anthocyanin dominantly.…”
Section: Discussionmentioning
confidence: 99%